2016
DOI: 10.1002/hep.28609
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C management in prisons: An insight into daily clinical practice in three major Italian correctional houses

Abstract: AO, et al. Screening diabetic patients for non-alcoholic fatty liver disease with controlled attenuation parameter and liver stiffness measurements: a prospective cohort study. Gut 2015;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 1 publication
1
16
0
2
Order By: Relevance
“…Previous experiences have demonstrated that HCV treatment in incarcerated populations is feasible and meets the standard criteria for cost-effectiveness [12,24]. A recent report describes the experience in three major Italian prisons of a program of test and treat chronic HCV inmates with DAAs only for those with advanced disease (F3-F4) according to Italian guidelines [7]. The "El Dueso" experience goes further in terms of extending treatments to all fibrosis stages, universal use of DAAs, and sustainability of the program over time, intending to become a real HCV-reservoir elimination program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiences have demonstrated that HCV treatment in incarcerated populations is feasible and meets the standard criteria for cost-effectiveness [12,24]. A recent report describes the experience in three major Italian prisons of a program of test and treat chronic HCV inmates with DAAs only for those with advanced disease (F3-F4) according to Italian guidelines [7]. The "El Dueso" experience goes further in terms of extending treatments to all fibrosis stages, universal use of DAAs, and sustainability of the program over time, intending to become a real HCV-reservoir elimination program.…”
Section: Discussionmentioning
confidence: 99%
“…lower (15.5% and 15.3%, respectively) [6]. Some intrinsic circumstances aggravate the problem, such as a substantial risk of HCV transmission during incarceration and after release, favored in part by an unawareness rate up to 25% [7].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…DAA treatment in prisoners is very attractive because it is effective, safe and short term. However, there are very few reports of its use in the prison environment: to our knowledge, only 1 letter, 2 congress presentations and 2 pharmacoeconomic studies have been published. Probably, the scarcity of results is related to the more limited access to treatment of inmates, for economic reasons .…”
Section: Discussionmentioning
confidence: 99%
“…In inmates the main cause of discontinuation was release from prison, in which case information regarding the completion of the treatment and the achievement of SVR was very often lost. The difficulty of continuing the treatment after release has often been cited 8,19,[26][27][28][29] and is the main obstacle to obtaining SVR when the treatment is initiated in prison. This problem was also cited by McDonald 20 and Bouteille-Gaillet, 21 who reported rates of missing cases due to release of 28% and 27%, respectively.…”
Section: Discussionmentioning
confidence: 99%